2002
DOI: 10.1046/j.1365-2036.2002.01253.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection, anti‐cagA antibodies and peptic ulcer: a case–control study in Italy

Abstract: Aim: To evaluate the association between infection with specific strains of Helicobacter pylori and peptic ulcer in patients referred for upper gastrointestinal endoscopy. Methods: One thousand, six hundred and twenty‐six consecutive dyspeptic patients, referred to one Endoscopy Unit in Bologna, Italy, were enrolled. For each participant, a blood sample was obtained for the measurement of distinct immunoglobulin G antibodies against H. pylori lysate and cytotoxin associated gene A (cagA). A case–control study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
(6 reference statements)
1
19
0
Order By: Relevance
“…It has recently become possible to detect antibodies for cagA proteins with ELISA methods [8,26]. Along with isolation of H. pylori, demonstration of cagA positivity with noninvasive methods could be helpful in some patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently become possible to detect antibodies for cagA proteins with ELISA methods [8,26]. Along with isolation of H. pylori, demonstration of cagA positivity with noninvasive methods could be helpful in some patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in Western countries have confirmed that infection with cagA-positive strains is associated with more severe gastritis and higher prevalence of peptic ulcer and gastric cancer [6,7]. However, studies in Far Eastern countries demonstrate equally high prevalence of cagA-positive strains in patients with peptic ulcer, gastric cancer, and nonulcer dyspepsia and in control subjects [8]. In Turkey, cagA positivity and the clinical outcome of H. pylori infection has been studied.…”
Section: Introductionmentioning
confidence: 95%
“…Helicobacter pylori ( H. pylori ), a microaerophilic, gram negative bacterium that colonises the mucous layer of the gastric epithelium, is the causative agent of type B gastritis, peptic ulcer, gastric cancer [13], and extradigestive diseases [4]. At least one-third of the world's population is infected with H. pylori .…”
Section: Introductionmentioning
confidence: 99%
“…In one case-control study (27) (Table II) the risk of DU and GU was higher in CagA positive subjects compared with seronegative subjects, but the odds ratio (OR) using both Cohort of health evaluation medical program markers (antibodies against H. pylori and anti-CagA antibodies) was similar. In another case-control study (28), serum CagA positive was higher in peptic ulcer patients than in controls, both groups being infected by H. pylori.…”
Section: Pathogenicity Island and The Cytotoxin Associated Antigen (Cmentioning
confidence: 90%